Pengaruh Pembiayaan Mudharabah dan Pembiayaan Musyarakah terhadap Laba Bersih pada PT. Bank Syariah Mandiri Periode 2013-2017 - Sri Monika (Universitas Batanghari Jambi, 2019)
This research aims to determine and analyze the effect of simultaneous and partial mudharabah financing and musyarakah financing on net income at PT. Bank Syariah Mandiri for the period 2008-2017. The analytical method used is multiple linear regression analysis. For statistical calculations using the SPSS version 20 computer program with the classic assumption test (normality test, autocorrelation test, multicolinearity test, heteroscedasticity test). Hypothesis testing uses the f test and t test and the coefficient of determination. The results of the research that has been carried out mudharabah financing and musyarakah financing have a simultaneous effect on net income because it is obtained from the f test the sig 0,043 value is smaller than 0,05 but based on the results on the t test the mudharabah financing affects net income while musyarakah financing does not affect net income. Keywords : Mudharbah financing, Musyarakah financing, and Net income